THE APPLICATION OF BEHAVIOR THERAPY MODEL FOR THE IMPROVEMENT OF SPEAKING ABILITY OF DYSARTHRIA PATIENTS - Gusdi Sastra; Amel Yanis; Ike Revilta; Handoko Handoko (Humaniora, 2016)
Research on behavior therapy has been conducted on patients with dysarthria, a disorder of articulation due to impairment of the central nervous system, which directly controls the activity of the muscles that play a role in the process of articulation in the pronunciation production. This study discusses three issues: lingual form made by people with dysarthria before getting behavior therapy, emotional influences on lexical and semantic knowledge of the patient, and the achievement of the model of behavior therapy applied to patients with dysarthria speech impairment. The theory used in this study was from Prins (2004) and the method of analysis applied is the method from Nunan (1992)combined with Sudaryanto (1993).The research found that there is an increased ability of patient to talk: nearly 40 percent of the index lingual knowledge or information, 20 percent of semantics, and 40 percent of feeling. Lingual index is significant as a means of therapy for patients with dysarthria. An increase in the speech ability improves confidence in facing social life.